LAMA WAKTU PENCEGAHAN SERANGAN Aeromonas hydrophilla PADA IKAN GABUS (Channa striata) YANG DIBERI PAKAN MENGANDUNG JINTAN HITAM (Nigella sativa) - Ahmad Fahrinaldi Aryadinata; Ade Dwi Sasanti; Yulisman Yulisman (Universitas Sriwijaya, 2021)
Black cumin (Nigela sativa) is immunostimulant that is able to improve the mechanism of cellular and humoral immunity response of fish. The aimed of this study was to determine the effect of the different injection times of Aeromonas hydrophilla after feeding with black cumin 3.5% for 14 days on snakehead on the prevalence, total leukocyte, hematocrit, survival rate and absolute growth of snakehead. All the test fish were fed with 3.5% black cumin for 14 days. Fish were fed three times a day at satiation. The treatment P1: injected A. hydrophilla at 10 days after feeding, P2: injected A. hydrophilla at 15 days after feeding and P3: injected with A. hydrophilla 20 days after feeding. The parameters observed were prevalence, total leukocyte, hematocrit, survival rate and absolute growth of snakehead. The results showed the treatment of the difference in injection time significantly effect on the prevalence but did not significantly effect on the survival rate and absolute growth of snakehead. Feeding containing 3.5% black cumin for 14 days can protect snakehead for 20 days after feeding. Prevalence of fish, total leukocyte, hematocrit, survival rate, length growth and weight growth fish in treatment P3, were 26.67%, 3.36 x 104sel.mm-3, 38%, 53%, 1.24 cm and 2.07 g, respectively. Keywords: A. hydrophilla, Black cumin, Snakehead.